Wafer-Scaled III-Nitrides Nanowire Photocathodes Enabled by Synergistic Dual-Electron Extraction for Efficient Solar-to-Hydrogen Conversion - Yang, Xudong; Liu, Yuying; Chen, Wei; Zhang, Tianle; Gu, Wengang; Liu, Xin; Luo, Yuanmin; Gao, Zhixiang; Li, Yang; Wang, Menglong; Wang, Weiyi; Long, Ran; et al. (Nano-Micro Letters, 2026)
Efficient, durable, and scalable photocathodes are indispensable for large-scale solar-to-hydrogen production. Notably, single-junction semiconductor photocathodes are attractive due to their structural simplicity, cost-effectiveness, and mature fabrication, yet they usually exhibit intrinsically poor carrier extraction efficiency. To address this challenge, we propose a synergistic “dual-electron extraction” strategy that fully unleashes the hydrogen evolution potential of single-junction p-InGaN nanowires. Remarkably, the optimized p-InGaN photocathode achieves a photocurrent density of −3.40 mA cm−2 at 0 V vs. RHE—representing a 37.8-fold enhancement over the pristine device—with an onset potential of 0.82 V vs. RHE, while sustaining stable hydrogen generation for over 300 h without additional protective layers. Specifically, an electron-blocking layer was incorporated within p‑InGaN nanowires to suppress electron backflow toward the substrate and promote transport to the nanowire/electrolyte interface. Furthermore, surface anion doping in InGaN nanowires significantly enhances the band bending of InGaN, which promotes interfacial electron transfer while simultaneously optimizing hydrogen adsorption energy, thereby accelerating the hydrogen evolution reaction rate. The proposed synergistic dual-electron extraction strategy markedly improves the electron utilization efficiency of single-junction InGaN nanowires, providing a novel pathway to address the intrinsic limitations of wafer-scale III-V nitride photoelectrodes. Highlights: 1 A scalable internal–external synergistic dual-electron extraction strategy is proposed, enabling rapid bulk-surface-electrolyte electron transport in single-junction p-InGaN nanowire for highly efficient photoelectrochemical hydrogen evolution. 2 Optimized single-junction p-InGaN photoelectrode exhibits a superior onset potential of 0.82 V vs. RHE and maintains continuous hydrogen generation for more than 300 h without protective coatings. 3 This material platform and optimization strategy possess wafer-scale scalability and manufacturing compatibility, providing new technical insights for photoelectrochemical hydrogen production with industrial application value.